Improving capacity utilization through material handling automation: a case study of a food processing plant. (2004)
This study is about the use of automated material handling system to eliminate bottlenecks on production line in order to achieve higher system capacity utilization. It was applied to the milling plant of a food processing company. Detailed study of the milling plant work system's parameters was carried out to give a basis for the selection of a suitable new transfer system. Facility layout analysis to determine floor space requirement as well as work system design analysis and cost/ benefits analysts were also used. A pneumatic conveyor system has been designed to replace manual handling in a critical portion of the flow line. Costs and benefits analysis indicate that an overall increase qf 30% in revenue at a cost of 8.4% increase in input resources is achievable if the proposed subsystem is installed. Productivity will also increase by 29% by the proposed automation.